Application of OASys approaches for Prophetic Food Ontology - Mohd Tawil, S.F.; Ismail, R.; Mazlan, A.A.; Fauziah Abdul Wahid; Norita Md. Norwawi (Universiti Sains Islam Malaysia, 2024)
Ontology is an established knowledge representation enriched with a semantic interpretation that offered a mechanism for sharing mutual ideas and understanding among the members of a related domain. Semantic interpretation provided by the ontology has a structure that could facilitate the presentation of information for the users. This paper presents the ontology construction of prophetic food specifically for Dates and Goats Milk by using the OASys approaches. The ontology content focusing on the dates attributes, the developing stages of dates, defect and diseases of dates, health benefits, its compositions, and the chain of operation. Besides, the ontology content for goat’s milk includes its nutrition, its cure for a medical problem, and the production. The construction of this ontology can be used to answer user queries, data integration to other applications as well as expand the ontology to a context mining semantic information retrieval search engine known as Naqli Aqli Integrated Search Engine (NAISE). This system is a query system based on integrated Naqli and Aqli knowledge heterogeneous sources on prophetic food.